Análise de contingências na programação de ensino em grupo para alunos de um curso de psicologia - Vedova, Juliana de Oliveira Dala (2009)
Issues related to individual and group instruction have been studied indicating the need for research in contingencies analysis of programmed instruction in order to verify the possibility of employing them in group settings. The intention of this study was to compare the teaching of some concepts of Experimental Behavior Analysis in a programmed instruction situation, referred to as instruction condition 1 (C1), and teaching by means of reading and discussion, referred to as instruction condition 2 (C2). In both cases, teaching was carried out with small groups of students. Thirty-five psychology students from two different classes of a private institution participated in this study, sixteen of which had classes in the morning, and nineteen of them had classes in the evening. The teaching content was based on some concepts about reinforcement. All the students were alternately submitted to both instruction conditions, so that the experimental design was ABAB. The only difference between the two groups was the starting point: while one group started with A (C1), the other started with B (C2), and proceeded alternating conditions throughout the process. The students performance was analysed based on three different evaluations: an initial content test (in order to ascertain how much previous knowledge the students had of the subject), a test at the end of each of the instructional conditions (adding up to four tests), and a final contest test in order to verify changes in performance after the application of all the instructional conditions. Twenty-three students concluded all the research activities. Both groups performed better in C1 than in C2. However, the analysis of the performance of students individually reveals particular results when comparing procedures C1 and C2, as well as when comparing performance participants who studied in the morning and those who studied in the evening. The results obtained for C1 are consistent with those found in the literature regarding the efficacy of the analysis of contingencies in programmed instruction, which is also observed in group settings. As to C2, although student performance was relatively lower than in C1, student progress on an individual basis was significant